Deflazacort versus prednisone/prednisolone for maintaining motor function and delaying loss of ambulation: A post HOC analysis from the ACT DMD trial. Issue 5 (27th September 2018) - Shieh, Perry B.; M intosh, Joseph; Jin, Fengbin; Souza, Marcio; Elfring, Gary; Narayanan, Siva; Trifillis, Panayiota; Peltz, Stuart W.; M donald, Craig M.; Darras, Basil T.; ,
ABSTRACT: Introduction : ACT DMD was a 48‐week trial of ataluren for nonsense mutation Duchenne muscular dystrophy (nmDMD). Patients received corticosteroids for ≥6 months at entry and stable regimens throughout study. This post hoc analysis compares efficacy and safety for deflazacort and prednisone/prednisolone in the placebo arm. Methods : Patients received deflazacort ( n  = 53) or prednisone/prednisolone ( n  = 61). Endpoints included change from baseline in 6‐minute walk distance (6MWD), timed function tests, estimated age at loss of ambulation (extrapolated from 6MWD). Results : Mean changes in 6MWD were ‐39.0 m (deflazacort; 95% confidence limit [CL], ‐68.85, ‐9.17) and ‐70.6 m (prednisone/prednisolone; 95% CL, ‐97.16, ‐44.02). Mean changes in 4‐stair climb were 3.79 s (deflazacort; 95% CL, 1.54, 6.03) and 6.67 s (prednisone/prednisolone; 95% CL, 4.69, 8.64). Conclusions : This analysis, limited by its post hoc nature, suggests greater preservation of 6MWD and 4‐stair climb with deflazacort vs. prednisone/prednisolone. A head‐to‐head comparison will better define these differences. Muscle Nerve 58 : 639–645, 2018